Intravenous Laser Blood Irradiation and Tocilizumab in a Patient with Juvenile Arthritis - Dragos Andrei Chiran; Michael Weber; Laura Marinela Ailioaie; Eovelina Moraru; Constantin Ailioaie; Daniela Litscher; Gerhard Litscher (Case Reports in Medicine)
This study presents effects of intravenous laser blood irradiation (ILBI) in a transient immunodeficiency patient with juvenile idiopathic arthritis (JIA) treated with an interleukin-6 receptor inhibitor (Tocilizumab). Biological agents induce JIA remission, but some patients do not respond favorably to this final therapeutic line of defense. ILBI was performed in a 16-year-old male patient, with JIA and transient immunodeficiency. When ILBI was introduced, the patient was receiving disease-modifying drugs, steroids, tocilizumab, and physical therapy. Because the disease was not well controlled, ILBI was applied in addition to other ongoing therapies. The patient underwent 1 session daily, and 10 successive sessions per month, repeated every 3 months, for 7 months. Patient evaluation was performed before ILBI was started and at 3, 6, 9, and 12 months after ILBI initiation, using the ACR Pediatric response. The outcome was evaluated using Pediatric 50, 70, and 90 responses and compared to initial status, after 3, 6, 9, and 12 months. At the end of study, the titre of IgA and IgG levels returned to normal. Synergistic anti-inflammatory effect of ILBI was evident, if applied additionally in combination with tocilizumab, in a patient with a therapy-resistant severe form of JIA and related subacute transient immunodeficiency.